Quranic Interpretation on Gender: A Study of Interpretations Through Maqāṣid Approach - Shaista Rassol; Showkat Hussain (LECTURES: Journal of Islamic and Education Studies, 2026)
The role and status of women in the Qur'an have been a crucial discourse because of diverse interpretative approaches with the classical and modern Muslim scholarship. Classical exegetes like al-Ṭabarī, Imam Qurtubi, and Ibn Kathīr often analysed verses about women within juridical and narrative contexts, reflecting the socio-historical circumstances of their era and perpetuating existing hierarchies. On the other hand, modern exegetes like Muhammad ʿAbduh, Muhammad Asad, and the Indian scholar Abul Kalam Azad strove to reinterpret these verses through the lens of intellectual inquiry, universal principles, and the pressing ethical demands of their society. The other perspective generated by the Muslim feminist scholars of the modern era like Amina Wadud and Asma Barlas, have developed women-centred hermeneutics based on gender justice. This study conducts a comparative analysis of specific verses related to creation, marriage, divorce, polygamy, and spiritual equality. Despite diverse interpretive approaches, the study focuses on the interpretations based on justice when viewed through maqāṣid (objectives) basis. The paper argues that gender inequities are not rooted in the Qur’an itself but in human interpretations across history. A maqāṣid-oriented approach upholds women as equal moral agents before God and emphasizes a holistic vision of their dignity. It highlights not only respect and equality but also safeguarding women’s spiritual accountability, intellectual agency, economic rights, and familial well-being.